PENERAPAN MODEL QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V.C SDN 016 SEKELADI KECAMATAN TANAH PUTIH KAB. ROKAN HILIR - Fitriyani, Fitriyani; Zulkifli, Zulkifli; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrak : this Research have go to to to level it result study class student IPS V.C SDN 016 Soil Sekeladi White with student's number many 10 student's people. this Research is done with 2 cycle, every cycle consist from 2 time meeting with 1 time repeating of daily. data Instrument collection to research this is teacher's observation sheet, student's observation sheet and result test study. the activity data analysiical-Result teacher to cycle meeting I first 58,33 % and second meeting to level become 75 %. To cycle meeting II first 83,33% and second meeting to level become 87,50%. Next the activity data analysiical-result student to cycle meeting I first 54,16% and second meeting to level become 62,50%. To cycle meeting II first 79,16% and second meeting to level become 83,33%. From this research result be obtained result study student to undergo leveling that is average result study student to base skor is 52,5 to level to cycle I become 68,0 to level again to cycle II 70,0 To completing study to base skor is 4 people ( 40 % ) to level to cycle I become 7 people ( 70 % ) and to level again to cycle II become 9 people ( 90 % ). With such can to be concluded that to be applied Model Quantum Teaching can to level it result study class student IPS V C SDN 016 Soil Sekeladi White.Key Word : Model Quantum Teaching , Result study IPS.